2009
DOI: 10.1152/ajpendo.90767.2008
|View full text |Cite
|
Sign up to set email alerts
|

Ligand-based gene expression profiling reveals novel roles of glucocorticoid receptor in cardiac metabolism

Abstract: Recent studies have documented various roles of adrenal corticosteroid signaling in cardiac physiology and pathophysiology. It is known that glucocorticoids and aldosterone are able to bind glucocorticoid receptor (GR) and mineralocorticoid receptor, and these ligand-receptor interactions are redundant. It, therefore, has been impossible to delineate how these nuclear receptors couple with corticosteroid ligands and differentially regulate gene expression for operation of their distinct functions in the heart.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
16
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 52 publications
4
16
1
Order By: Relevance
“…Whether the Dmd and RyR2 genes are primary or secondary targets of GR regulation is currently unknown. However, Klf15, Ptgds, and MuRF1 are bona fide glucocorticoid-responsive target genes that are induced by activated GR (11)(12)(13)(14). Accordingly, in the absence of an intact GR signaling pathway in cardiomyocytes, the expression of these genes is significantly repressed.…”
Section: Discussionmentioning
confidence: 99%
“…Whether the Dmd and RyR2 genes are primary or secondary targets of GR regulation is currently unknown. However, Klf15, Ptgds, and MuRF1 are bona fide glucocorticoid-responsive target genes that are induced by activated GR (11)(12)(13)(14). Accordingly, in the absence of an intact GR signaling pathway in cardiomyocytes, the expression of these genes is significantly repressed.…”
Section: Discussionmentioning
confidence: 99%
“…For example, glucocorticoids suppress COX-2 expression in immune cells, whereas they increase COX-2 expression in cardiomyocytes. 6,14,15 The induction of COX-2 is cardioprotective in the context of I/R injury and post-myocardial infarction cardiac remodeling. However, the treatment of acute myocardial infarction with glucocorticoids has yielded inconsistent and conflicting results.…”
Section: Discussionmentioning
confidence: 99%
“…15,16), or ALD (17). Unexpectedly, we found that the expression of genes that encode 2 key enzymes in a common pathway of prostaglandin biosynthesis were upregulated by glucocorticoids via the GR in cardiomyocytes: phospholipase A2 group IVA (Pla2g4a; encoding cytosolic calcium-dependent phospholipase A2 [cPLA2]), which belongs to the class of cPLA2s that preferentially cleave arachidonic acid from membrane phospholipids; and pros-…”
Section: Introductionmentioning
confidence: 90%